Oscillation and nonoscillation of second order half-linear differential equations - Yong Zhou; Chen, X.W. (Нелінійні коливання, 2012)
We consider the oscillation and nonoscillation of second order half-linear differential equation. By using some new technique, we establish new oscillation and nonoscillation criteria which extend and improve some known results for second order linear differential equation. Розглянуто осциляцiйнi та неосциляцiйнi напiвлiнiйнi диференцiальнi рiвняння другого порядку. З використанням нової технiки встановлено новi критерiї наявностi та вiдсутностi осциляцiй. Цi критерiї поширюють та покращують вiдомi результати для лiнiйних диференцiальних рiвнянь другого порядку.